KINERJA PT. POS INDONESIA (Studi Kasus Pengiriman Paket Pos di Kota Pekanbaru ) - Tsana Kamilia Aini; Harapan Tua RFS (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Organizational performance is crucial to success in running the organization. With good performance and supported by qualified facilities, it is certain that the organization can achieve the vision and mission that has been made to improve its quality. To measure and assess the performance of an organization is required a clear performance indicators. As a guideline in the assessment of organizational performance, can be seen and based on the purpose of the establishment of the organization, as well as PT. Pos Indonesia branch of Pekanbaru City. At PT. Pos ndonesia Ibranch Pekanbaru in the previous year of this organization has improved the performance of the organization but can still be defeated by its competitors. Increased competitors in postal package services as well as changes in fumgsi letters by mobile phones and drafts replaced by banks make a big impact on the number of production and the number of customer complaints PT. Pos Indonesia branch of Pekanbaru City. The postal party is required to compete with its competitors from the private sector.This research was conducted at Post Office branch of Pekanbaru City with the aim to know how the performance of service package at Post Office of Pekanbaru City and to know the factors that become obstacle in post performance Pekanbaru City. This research uses Dwiyanto theory in Sudarmanto with qualitative research method. In collecting data used observation data collection techniques and interviews to the research informants. After the data collected and then drawn conclusions and analyzed by using qualitative descriptive data analysis techniquesThe conclusion of this research is the performance of postal package service at Pekanbaru post office branch is not good enough, due to some things that have not been implemented optimally, especially on productivity indicator, service quality and responsiveness in achieving each work target. However, in terms of responsibilitas and accountability is good enough. The factors that affect the performance of postal package services in Pekanbaru City are technology, initiative, human resource management and cooperation, where these factors can encourage the improvement of more excellent results.Keywords: performance, post Indonesia, postal package services